Dialogical modality as a factor of implementation of the effecting text function in the English language - Akhramenko, Liubov S. (Journal of the Belarusian State University. Philology, 2020)
The object of the study is a dialogical modality that expresses the author’s attitude to the addressee. The means and pragmatic functions of the dialogical modality, with the help of which the author indirectly suggests his own point of view to the addressee, are considered. The novelty of the article lies in the fact that textual modality expresses not only the relation of the content of the statement to reality and the relation of the author to the content of the statement, but also the relation of the author to the addressee. Consequently, the semantic volume and arsenal of means of its expression expands significantly: modality can be expressed not only by grammatical, but also lexical, syntactic, phraseological, stylistic means. The study of the dialogical modality expands the list of language means by which the author can indirectly convince the addressee of the correctness of his own viewpoint and, consequently, realize the author’s pragmatic attitude.
Keywords: dialogical modality; text; author; addressee; pragmatic function